Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.2460/javma.2000.216.687
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enteric zoonotic organisms in cats

Abstract: Enteric zoonotic organisms were detected in feces of 13.1% of cats, suggesting that cats, particularly those in homes of immunocompromised humans, should be evaluated for enteric zoonotic organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
100
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(121 citation statements)
references
References 33 publications
16
100
4
Order By: Relevance
“…33 In a study in Poland, up to 10% of the cats tested positive for Campylobacter spp. in the rectal swabs, with the predominance of C. jejuni.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33 In a study in Poland, up to 10% of the cats tested positive for Campylobacter spp. in the rectal swabs, with the predominance of C. jejuni.…”
mentioning
confidence: 99%
“…Studies in Germany and USA have shown that 1 to 2% of the cats may have Salmonella in their fecal samples. 33,48 A wide range of serovars, including S. Typhimurium is found in cats. 49 Van Immerseel et al 50 examined the excretion of Salmonella by pet cats and found that some of the excreted serotypes including Typhimurium were resistant to many important antimicrobial drugs.…”
mentioning
confidence: 99%
“…Dogs less than 6 months of age are affected more often than the adults. By comparison, in a report of Cryptosporidium in cats, 50% of infected cats showed diarrhea symptoms (Hill et al, 2000). Zoonotic cryptosporidiosis from exposure to pets has not been documented in healthy adults but transmission of (bovine) C. parvum from companion (cats, dogs) to HIV-infected persons has been reported (Meisel et al, 1976).…”
Section: Infection In Humans and Zoonotic Importancementioning
confidence: 99%
“…These intracellular parasites of the genus Cryptosporidium (Apicomplexa) infect vertebrates, including humans, companion and farm animals, wild animals, birds and reptiles (de Oliveira et al, 2012;Fayer et al, 2000). Recently, the major concerns about the public health dangers of pet ownership have increased considerably, and while many potentially zoonotic organisms are associated with cats, enteric pathogens are of particular concern (Hill et al, 2000;Abarca et al, 2011). The majority of humans infections are caused by C. hominis and C. parvum.…”
Section: Introductionmentioning
confidence: 99%